Building Partner Capacity to Combat Weapons of Mass Destruction - Moroney, Jennifer D. P. (RAND Corporation, 2009)
Limited resources, access, and incomplete knowledge of weapons of mass destruction (WMD) threats create a need for working with appropriate partner countries around the world to address these challenging threats. This monograph outlines and then applies a four-step process for developing regional approaches to building partner capacity (BPC) to combat WMD.